2022
DOI: 10.1111/codi.16397
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in functional outcomes of stapled and hand‐sewn ileal pouch‐anal anastomosis for ulcerative colitis and familial adenomatous polyposis

Abstract: Aim Little is known about how ileal pouch‐anal anastomosis (IPAA) influences anorectal manometric data. This study aimed to clarify temporal changes in anorectal manometric data and faecal incontinence in IPAA. Methods We examined 32 patients with ulcerative colitis (UC) or familial adenomatous polyposis (FAP) undergoing restorative proctocolectomy with stapled or hand‐sewn IPAA. Maximum resting pressure (MRP) and maximum squeezing pressure (MSP) were analysed before and 1–3, 6–9, and 12–24 months after IPAA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Five studies were excluded for the following reasons 13 - 16 : 1 study included patients undergoing stapled anastomosis and compared high with low anastomosis, 13 1 study included only patients undergoing a hand-sewn anastomosis, 14 1 study included patients with rectal cancer, 15 1 study compared the outcomes of the reversal loop ileostomy, 16 and 1 study was a narrative review. 17 We then retained 31 trials 18 - 48 : 3 RCTs, 39 , 40 , 44 5 prospective clinical trials, 19 - 23 and 24 CCTs. 18 , 24 - 38 , 41 - 43 , 45 - 48 The demographic data of the studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were excluded for the following reasons 13 - 16 : 1 study included patients undergoing stapled anastomosis and compared high with low anastomosis, 13 1 study included only patients undergoing a hand-sewn anastomosis, 14 1 study included patients with rectal cancer, 15 1 study compared the outcomes of the reversal loop ileostomy, 16 and 1 study was a narrative review. 17 We then retained 31 trials 18 - 48 : 3 RCTs, 39 , 40 , 44 5 prospective clinical trials, 19 - 23 and 24 CCTs. 18 , 24 - 38 , 41 - 43 , 45 - 48 The demographic data of the studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 17 We then retained 31 trials 18 - 48 : 3 RCTs, 39 , 40 , 44 5 prospective clinical trials, 19 - 23 and 24 CCTs. 18 , 24 - 38 , 41 - 43 , 45 - 48 The demographic data of the studies are summarized in Table 1 . These studies included 8872 patients, 4871 patients in the stapled group, and 4038 hand-sewn group, and were published between 1991 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…In many previous studies, most comparisons between stapled and hand-sewn IPAA have focused on postoperative complications or functional outcomes [ 21 23 ]. Regarding short-term prognosis, a previous national study in Japan has reported that the 5-year OS is similar between stapled and hand-sewn IPAA [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…General information regarding the enrolled patients was collected, including sex, age at UC diagnosis, past medication history, disease extent according to the Montreal classification, disease manifestation based on the Truelove-Witts classification [ 9 ], presence of extraintestinal manifestations, and more. Baseline measurements included BMI, ESR, serum CRP, Hb and albumin (ALB) levels, fecal calprotectin levels, Inflammatory Bowel Disease Questionnaire (IBD-Q) score [ 10 ], and self-rated anxiety and depression assessed using the Zung Self-Rating Anxiety/Depression Scale (SAS/SDS) score, Cleveland Clinic Fecal Inconsistency (CCFI) score [ 11 ], and Ulcerative Colitis Endoscopic Index of Severity (UCEIS) score [ 12 ]. Notably, special attention was directed towards rectal inflammation during endoscopic examinations, with endoscopies performed within the preceding three months being deemed sufficient.…”
Section: Methodsmentioning
confidence: 99%